Sensitive Immunodetection of Severe Acute Respiratory Syndrome Coronavirus 2 Variants of Concern 501Y.V2 and 501Y.V1. (23rd May 2021) - Barlev-Gross, Moria; Weiss, Shay; Paran, Nir; Yahalom-Ronen, Yfat; Israeli, Ofir; Nemet, Ital; Kliker, Limor; Zuckerman, Neta; Glinert, Itai; Noy-Porat, Tal; Alcalay, Ron; Rosenfeld, Ronit; et al.
Abstract: Emerging severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants may influence the effectiveness of existing laboratory diagnostics. In the current study we determined whether the British (20I/501Y.V1) and South African (20H/501Y.V2) SARS-CoV-2 variants of concern are detected with an in-house S1-based antigen detection assay, analyzing spiked pools of quantitative reverse-transcription polymerase chain reaction–negative nasopharyngeal swab specimens. The assay, combining 4 monoclonal antibodies, allowed sensitive detection of both the wild type and the variants of concern, despite accumulation of several mutations in the variants' S1 region—results suggesting that this combination, targeting distinct epitopes, enables both specificity and the universality. Abstract : Antigen-based point-of-care tests are implemented worldwide for detection of coronavirus disease 2019. A recently developed S1-based assay enabled sensitive and accurate detection of emerging severe acute respiratory syndrome coronavirus 2 variants of concern in nasopharyngeal swab samples.